2016
DOI: 10.1161/atvbaha.116.306925
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI as a Therapeutic Target

Abstract: Factor XIa is a plasma serine protease that contributes to thrombin generation primarily through proteolytic activation of factor IX. Traditionally considered part of the intrinsic pathway of coagulation, several lines of evidence now suggest that factor XIa serves as an interface between the vitamin-K dependent thrombin generation mechanism and the pro-inflammatory kallikrein-kinin system, allowing the two systems to influence each other. Work with animal models and results from epidemiologic surveys of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 41 publications
1
102
0
Order By: Relevance
“…Since factor XI (FXI[a]) augments thrombin generation, in part by synergizing tissue factor-mediated procoagulant activity 50 , FXI inhibition strategies to reduce thrombosis have received considerable attention (reviewed in 51 ). These approaches include conventional anti-FXI inhibitory antibodies, as well as technology in which antisense oligonucleotides (ASOs) result in the specific degradation of a target mRNA and corresponding reduction in target protein level.…”
Section: Effects Of Antithrombotic and Hemostatic Agents On Fibrinmentioning
confidence: 99%
“…Since factor XI (FXI[a]) augments thrombin generation, in part by synergizing tissue factor-mediated procoagulant activity 50 , FXI inhibition strategies to reduce thrombosis have received considerable attention (reviewed in 51 ). These approaches include conventional anti-FXI inhibitory antibodies, as well as technology in which antisense oligonucleotides (ASOs) result in the specific degradation of a target mRNA and corresponding reduction in target protein level.…”
Section: Effects Of Antithrombotic and Hemostatic Agents On Fibrinmentioning
confidence: 99%
“…Recent epidemiological and animal studies have suggested that FXI, a coagulation factor upstream to thrombin and FXa, is a potential target to achieve this goal. 11 This review outlines the rationale for targeting upstream coagulation factors, identifies FXI as the ideal candidate, summarizes current progress, and highlights what is in the pipeline for the next era of anticoagulants.…”
Section: See Insight Into Jeffrey I Weitz On Page 311mentioning
confidence: 99%
“…However, FXI-deficient individuals are more prone to bleeding in the nasopharyngeal and reproductive tracts than in other sites, suggesting that tissues with high fibrinolytic activity may be more dependent on FXI than others. 11 Furthermore, FXI levels are poorly correlated with the risk of bleeding. 65 Despite these limitations, however, FXI remains an attractive target for novel anticoagulant strategies.…”
Section: Potential Indications For Fxi-directed Therapiesmentioning
confidence: 99%
“…Congenital FXI deficiency protects patients from stroke and venous thromboembolism, and is only associated with minor bleeding episodes. 9,10 Additionally, blockade of FXII might be protective in microorganism-driven thrombotic complications accompanying sepsis, as inhibition of FXII activation of FXI reduced thrombotic complications in animal models of sepsis. 5,9 Here, we sought to better understand whether FXII and FXI differentially regulate the physical biology of fibrin networks.…”
Section: Discussionmentioning
confidence: 99%